1, 2, 3-Triazole derivatives as antitubercular agents: synthesis, biological evaluation and molecular docking study1. Issue 6 (10th June 2015) - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Nawale, Laxman; Sarkar, Dhiman; Kalam Khan, Firoz A.; Sangshetti, Jaiprakash N.; Shingate, Bapurao B.
<x xml:space="preserve">Abstract</x> A library of thirty one 1, 2, 3-triazole derivatives efficiently prepared via click chemistry and evaluated for their antitubercular, antioxidant, and cytotoxic activities.